Research progress of EZH2 in non-tumor renal diseases - Wang Hui; Wang Ting-ting; Liu Hong-bao (Linchuang shenzangbing zazhi)
The enhancer of zeste homolog 2 （EZH2） is a histone H3 lysine 27 methyltransferase， with an established role in various kidney diseases. This article reviewed the research progress of EZH2 in non-tumor kidney diseases by searching and reviewing relevant literatures in recent years， thus providing references for future studies.